Cutaneous lesions and other non-endocrine manifestations of Multiple Endocrine Neoplasia type 1 syndrome - Pierotti, Laura; Pardi, Elena; Dinoi, Elisa; Piaggi, Paolo; Borsari, Simona; Della Valentina, Simone; Sardella, Chiara; Michelucci, Angela; Caligo, Maria Adelaide; Bogazzi, Fausto; Marcocci, Claudio; Cetani, Filomena (Frontiers in Endocrinology, 2023)
Multiple Endocrine Neoplasia type 1 is a rare genetic syndrome mainly caused by mutations of the MEN1 gene and characterized by a combination of several different endocrine and nonendocrine manifestations. The objective of this study was to describe cutaneous lesions and other nonendocrine manifestations of MEN1 in a well-characterized cohort of patients with familial (F) and sporadic (S) MEN1, compare the prevalence of these manifestations between the two cohorts, and investigate the correlation with MEN1 mutation status. We collected clinical data of 185 patients (106 index cases and 79 MEN1 mutation-positive relatives) with familial and sporadic MEN1 syndrome followed at the Endocrine Unit of Pisa from 1997 to 2022. The prevalence of angiofibromas was significantly higher in F-MEN1 than in S-MEN1, both in the whole (p<0.001) and index cases (p=0.003) cohorts. The prevalence of lipomas was also significantly higher in F-MEN1 than in S-MEN1 (p=0.009) and in MEN1 mutation-positive than MEN1 mutation-negative (p=0.01) index cases. In the whole cohort, the prevalence of lipomas was significantly higher in MEN1 mutation-positive compared to MEN1 mutation-negative patients (OR=2.7, p=0.02) and in F-MEN1 than in S-MEN1 (p=0.03) only after adjustment for age. No significant differences were observed for the other nonendocrine manifestations between the two cohorts. Hibernoma and collagenoma were each present in one patient (0.5%), meningioma and neuroblastoma in 2.7% and 0.5%, respectively. Gastric leiomyoma was present in 1.1% of the patients and uterine leiomyoma in 14% of women. Thyroid cancer, breast cancer, lung cancer, basal cell carcinoma, melanoma, and colorectal cancer were present in 4.9%, 2.7%, 1.6%, 1.6%, 2,2%, and 0.5% of the whole series, respectively. We found a significant higher prevalence of angiofibromas and lipomas in F-MEN1 compared with S-MEN1. Both these manifestations were significantly more frequent in MEN1 mutation-positive compared to MEN1 mutation-negative patients.